Telephone versus in-person intake assessment for bereavement intervention: Does efficiency come at a cost?. Issue 2 (7th February 2016) - Newsom, Catherine; Schut, Henk; Stroebe, Margaret; Birrell, John; Wilson, Stewart
ABSTRACT: Standardized, evidence-based risk assessment is an important component in providing effective bereavement care. E-health intake assessments have been offered alongside or instead of in-person assessments, although evidence concerning the equivalence of assessment results is lacking. This article examines differences between a semistructured intake assessment for grief intervention conducted over the telephone ( n  = 330) and in-person ( n  = 115). Differences in scores and clinical implications were evaluated. Although composite assessment scores were lower in the telephone condition, further examination revealed this occurred in the semistructured assessment of risk of complications, not the structured grief symptom assessment. Implications for care provision are discussed.